Trehalose induces bladder smooth muscle hypercontractility in mice: involvement of oxidative stress and cellular senescence - Lemos, Guilherme; Fernandes, Cícera Madri Alves de Souza; Watanabe, Ingrid Kazue Mizuno; Delbin, Maria Andreia; Silva, Fábio Henrique; Calmasini, Fabiano Beraldi (Frontiers in Physiology, 2025)
Autophagy, a conserved catabolic process, is critical for cellular homeostasis and its dysregulation has been implicated in a number of conditions including hypertension, obesity and bladder dysfunctions. The autophagy inducer trehalose has shown promise in treating diseases; however, some studies have reported detrimental effects in vascular tissue under health conditions. In the bladder, the effects of trehalose remain unclear. Therefore, in the present study, male C57BL6/JUnib mice (8 weeks old) were divided into control and trehalose-treated groups (120 mg/mouse/day via gavage) for 4 weeks. After treatment, bladders were harvested for functional, biochemical, and molecular analyses. The trehalose treatment increased the bladder smooth muscle (BSM) contractility to carbachol (CCh), without altering relaxation response to isoproterenol. The CCh-induced BSM hypercontractility was completely abolished by the in vitro incubation of apocynin and diphenyleneiodonium (DPI), implicating NADPH oxidase-derived reactive oxygen species (ROS) on this process. Accordingly, increased levels of superoxide anion (O2-) were found in the urothelial layer, but not in BSM, of trehalose-treated mice. Trehalose also increased senescence-associated β-galactosidase activity in the bladder but failed to upregulate autophagy-related proteins LAMP1 and Beclin-1 in the bladder. Collectively, we show for the first time that trehalose induces BSM hypercontractility in mice, linked to increased levels of O2- and senescent cell, independently of autophagy activation. Therefore, trehalose administration is an effective model for studying BSM hypercontractility in mice, particularly associated with oxidative stress and cellular senescence.